Chunsheng Yang, Yiping Zhang, Wayne Wenchao He, L2 Acquisition of Chinese de Structures: A Comparative Study - Wenhua Jin; Chunsheng Yang; Yiping Zhang; Wayne Wenchao He (Journal of the National Council of Less Commonly Taught Languages)
This study examined the acquisition of three Chinese de structures, i.e. Nominalization, Cleft, and Relative Clause, by forty-three English speaking Chinese learners from three universities in the US. Our results showed that while patterns shared by all schools were multifold, interschool variations were evident in each of the dimensions examined. Findings of this study shed new light on the understanding of L2 acquisition of Chinese de structures, revealing its general across-the-board patterns, providing independent evidence for the much-debated easiness ranking of Chinese relative clauses from the perspective of the nominalization acquisition, and presenting new info for L2 Chinese feature processing. Several factors were identified as significant role players in the acquisition process: explicit grammar instruction, learner motivation, native language transfer, avoidance strategy, feature configurations in L1, etc., providing practical implications for the field of L2 Chinese and second language acquisition in general as well.